Copaiba oil minimizes inflammation and promotes parenchyma re-epithelization in acute allergic asthma model induced by ovalbumin in BALB/c mice - Caputo, Ludmila de Souza; Alves, Carolina de Lima; Laranjeira, Inês Martins; Fonseca-Rodrigues, Diana; da Silva Filho, Ademar Alves; Dias, Alberto Carlos Pires; Pinto-Ribeiro, Filipa; Pereira Junior, Olavo dos Santos; de Paula, Ana Claudia Chagas; Nagato, Akinori Cardozo; Corrêa, José Otávio do Amaral (Frontiers in Pharmacology, 2024)
This study aimed to investigate the effect of copaiba oil (e.g., Copaifera langsdorffii) at doses of 50 and 100 mg/kg on certain mediators of acute lung inflammation GATA3, FOXP3, STAT3, and TBET) and early mechanisms of lung remodeling (degradation of elastic fiber tissues, collagen deposition, and goblet cell hyperplasia). Using an ovalbumin-induced acute allergic asthma model in BALB/c mice, we analyzed the inflammatory mediators through immunohistochemistry and the mechanisms of lung remodeling through histopathology, employing orcein, Masson's trichrome, and periodic acid-Schiff staining. Copaiba oil treatment (CO) reduced IL-33 and increased FOXP3 by stimulating the FOXP3/GATA3 and FOXP3/STAT3 pathways. Additionally, it upregulated TBET, suggesting an additional role in controlling GATA3 activity. In the respiratory epithelium, CO decreased the fragmentation of elastic fibers while increasing the deposition of collagen fibers, favoring epithelial restructuring. Simultaneously, CO reduced goblet cell hyperplasia. Although additional research is warranted, the demonstrated anti-inflammatory and re-epithelializing action makes CO a viable option in exploring new treatments for acute allergic asthma.